Pengaruh Filsafat Pendidikan Humanistik terhadap Kesejahteraan Psikologis dan Kepuasan Belajar Mahasiswa di Universitas Bina Bangsa - Rifal Kurniawan Jaki; Desty Endrawati Subroto; Eni Sutianingsih; Nauratu Syifa; Desiska (PT. Penerbit Tiga Mutiara, 2025)
The humanistic approach in higher education plays a crucial role in enriching students' learning experiences, both academically and emotionally, with a focus on the holistic development of individuals. This approach emphasizes the importance of human values, character building, and empowering students in the learning process. This study aims to explore the relationship between humanistic educational philosophy, psychological well-being, and students' learning satisfaction at Bina Bangsa University. By paying attention to the needs, interests, and potential of each student, the humanistic approach creates an inclusive learning environment that supports personal development. The results of the study show that this approach can enhance motivation, creativity, and critical thinking skills in students through interactive learning methods such as discussions, debates, and practical work. Furthermore, the humanistic approach also has a positive impact on students' mental well-being by creating an emotionally safe classroom atmosphere, reducing stress, and anxiety. Students feel more valued and supported in their personal development. However, challenges arise when educators fail to provide clear explanations or adequate guidance before assigning tasks or homework, which can increase pressure on students. In conclusion, this study emphasizes that the humanistic approach is essential in creating a meaningful learning experience, which not only focuses on academic achievement but also on character development and psychological well-being. Therefore, the application of humanistic principles in higher education is key to creating a more relevant, holistic education that supports the balance between academic achievement and personal development.